VO#12 - Adjustment unit price for damp proofing work in raft, pile cap, H-steel and king post - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the VO#12 adjustment unit price for damp proofing work in raft, pile cap, H-steel and king post of BRACU new campus project site.